Textese and its Impact on the English Language - Thakur, Rameshwar (Journal of NELTA, 2021)
The growing interests of college students towards using Facebook (FB) features have invented newer texts for a faster online communication. Such unique textese and digitalese reside in their minds and hearts. Many scholars, therefore, currently advocate for exploring a new avenue to adapt certain linguistic contents (LCs) of FB in promoting and developing a language. Amidst, the LCs of such social networking sites allow users to entertain better interactions. Nevertheless, their indiscriminate use exerts threats to the existing body of the English Language (EL). In this context, this qualitative study tries to reconnoitre typical characteristics of textese based on purposively selected observation data from FBs of 20 college students and documentary data from published journals or books. It further analyzes how such contents aﬀect phonological, morphological, syntactic and semantic levels of the EL. The study concludes that the LCs impose problems to the EL; however, they require integrations into current form of the EL without causing serious problems because of their influences on netizens.